Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America - Grisales, Diana; de Carvalho, Claudio J. B. (Zootaxa, 2019)
In the neotropics, vegetation formations at high elevations are often unique, with their own characteristic vegetation because of unique and complex evolutionary histories. The complexity of the biogeographic and ecological structure of the fauna is demonstrated by the specialized fauna and flora occurring in these regions. Fanniidae (Diptera) is one of these specialized groups that became very diversified in the highlands. Currently, of the 91 species of Fanniidae in the Neotropical region, 43 (8 Euryomma, 35 Fannia) occur exclusively in Andean and Central American highlands. Here, we increase that highland diversity by describing 14 new species from 1000–4150 m.a.s.l. in the Andes and Central America: Fannia awa sp. nov., F. bari sp. nov., F. boruca sp. nov., F. bribri sp. nov., F. huetare sp. nov., F. humahuaca sp. nov., F. kabekwa sp. nov., F. palta sp. nov., F. polleti sp. nov., F. quillacingas sp. nov., F. teribi sp. nov., F. terraba sp. nov., F. tsachilas sp. nov. and F. yukpa sp. nov. We also provide an identification key for male specimens and diagnoses and descriptions of the species, along with photographs and illustrations of the male terminalia. New records and updated distributions are also provided for the Andean species.